2022
DOI: 10.1002/jia2.26021
|View full text |Cite
|
Sign up to set email alerts
|

Modelling cervical cancer elimination using single‐visit screening and treatment strategies in the context of high HIV prevalence: estimates for KwaZulu‐Natal, South Africa

Abstract: Introduction In settings with high HIV prevalence, cervical cancer incidence rates are up to six‐fold higher than the global average of 13.1 cases per 100,000 women‐years. To inform strategies for global cervical cancer elimination, we used a dynamic transmission model to evaluate scalable screening and treatment strategies, accounting for HIV‐associated cancer risks and weighing prevention gains against overtreatment. Methods We developed a dynamic model of HIV‐HPV co‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…Further studies are needed to evaluate if the establishment of a dedicated cervical screening service within our hospital for women at high risk would improve screening rates as it has in other studies. 16 , 17 , 18 Considering the prevalence of HIV in South Africa and the known links between HIV and cervical cancer, an HIV clinic serves as an ideal site for cervical cancer screening. Alternatively, an organised referral system to a dedicated screening facility would greatly improve the number of women referred for screening – this could be initiated through utilisation of currently available gynaecology services in our hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are needed to evaluate if the establishment of a dedicated cervical screening service within our hospital for women at high risk would improve screening rates as it has in other studies. 16 , 17 , 18 Considering the prevalence of HIV in South Africa and the known links between HIV and cervical cancer, an HIV clinic serves as an ideal site for cervical cancer screening. Alternatively, an organised referral system to a dedicated screening facility would greatly improve the number of women referred for screening – this could be initiated through utilisation of currently available gynaecology services in our hospital.…”
Section: Discussionmentioning
confidence: 99%
“…We used the DRIVE (Data-driven Recommendations for Interventions against Viral InfEction) model [ 13 ], a dynamic, compartmental model of HIV and HPV transmission and disease progression, to project cervical cancer and HIV outcomes for the province of KwaZulu-Natal, South Africa between the years 2001 and 2071. The model population was stratified by age, gender, sexual activity risk group, and infection and disease status.…”
Section: Methodsmentioning
confidence: 99%
“…These differences, along with the heightened risk of cervical cancer among women living with HIV, highlight the importance of cervical cancer prevention and treatment guidelines tailored by HIV status. Recent modeling studies predicted that increasing vaccination or screening frequency for women living with HIV can significantly decrease near-term cervical cancer incidence [ 6 , 13 , 14 ]. A comparative modeling study additionally demonstrated reduced relative cancer incidence among women living with HIV with focused interventions, but assumed idealized coverage levels of precancer and cancer treatment and 100% precancer treatment efficacy [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,3 To achieve the goal of the World Health Organization (WHO) of eliminating CC, countries in sub-Saharan Africa (SSA) must scale up access to primary, secondary, and tertiary prevention measures, especially for girls and WLHIV. [4][5][6] To improve CC control programs, clinicians, researchers, and policymakers need high-quality routine health facility data, 7,8 which can be collected by monitoring each step of the path that people take through the health system. To create a monitoring plan for cancer control, each sequential step through a complex health system must be quantified within the framework of a cascade 9 and indicators must be specified for each step.…”
Section: Introductionmentioning
confidence: 99%